Reproductive factors and exogenous hormone use in relation to risk of glioma and meningioma in a large European cohort study. - Michaud, D; Gallo, V; Schlehofer, B; Tjønneland, A; Olsen, A; Overvad, K; Dahm, C; Kaaks, R; Lukanova, A; Boeing, H; Schütze, M; Trichopoulou, A; et al. (2010)
BACKGROUND: The etiologies of glioma and meningioma tumors are largely unknown. Although reproductive hormones are thought to influence the risk of these tumors, epidemiologic data are not supportive of this hypothesis; however, few cohort studies have published on this topic. We examined the relation between reproductive factors and the risk of glioma and meningioma among women in the European Prospective Investigation into Cancer and Nutrition (EPIC). METHODS: After a mean of 8.4 years of follow-up, 193 glioma and 194 meningioma cases were identified among 276,212 women. Information on reproductive factors and hormone use was collected at baseline. Cox proportional hazard regression was used to determine hazard ratios (HR) and 95% confidence intervals (95% CI). RESULTS: No associations were observed between glioma or meningioma risk and reproductive factors, including age at menarche, parity, age at first birth, menopausal status, and age at menopause. A higher risk of meningioma was observed among postmenopausal women who were current users of hormone replacement therapy (HR, 1.79; 95% CI, 1.18-2.71) compared with never users. Similarly, current users of oral contraceptives were at higher risk of meningioma than never users (HR, 3.61; 95% CI, 1.75-7.46). CONCLUSION: Our results do not support a role for estrogens and glioma risk. Use of exogenous hormones, especially current use, seems to increase meningioma risk. However, these findings could be due to diagnostic bias and require confirmation. IMPACT: Elucidating the role of hormones in brain tumor development has important implications and needs to be further examined using biological measurements.